Comparison of Helsinki CT and Rotterdam CT Scoring Systems As Prognostic Factors of Brain Injury - Andi Asadul Islam; Andi Ihwan; Junus Asiu Bulu Baan; Firdaus Hamid; Kenny Edward Yap (Nusantara Medical Science Journal, 2021)
Introduction: Brain injury is a major cause of death and disability. Computerized Tomography (CT) scanning of the brain is essential for diagnostic screening in need of neurosurgical intervention and also provide information about patient prognosis. Methods: This study is a retrospective study design to assess the comparison of the CT scan scoring system of the head with the prognostic factors of brain injury. Head CT Scans were assessed according to the following Rotterdam and Helsinki CT Scores. All patients were managed according to standard guidelines. Surgery was performed as indicated. The primary objective was mortality assessed using the Glasgow Outcome Scale (GOS) at discharge and 3 months after. Results: Altogether, 60 patients were included. The results of the ROC analysis of the two CT scoring systems, the Helsinki score provided a better sensitivity score> 80% compared to the Rotterdam score, with a positive predictive value of around 74% each for assessing the outcome (GOS) of brain injury patients Conclusions: The Helsinki score scoring system provides a better sensitivity compared to the Rotterdam score